AUDIT^2 – A Clinical Audit of the Alcohol Assessment and Management in the Southern Gambling Service – First Round Results - Filipa M.A.A. Teixeira; Julia M.A. Sinclair; Samuel R. Chamberlain; Konstantinos Ioannidis (BJPsych Open, 2025)
Aims: The audit aimed to evaluate assessment, intervention, and signposting for alcohol use problems in people with gambling disorder presenting to the Southern Gambling Service (SGS).